Estimation of fatigue strength under multiaxial cyclic loading by varying the critical plane orientation - Marta Kurek; Tadeusz Łagoda; Andrea Carpinteri; Sabrina Vantadori (Fracture and Structural Integrity)
The main purpose of this paper is to examine the influence of the critical plane orientation on the estimated fatigue strength of metals under multiaxial loading. The algorithm employed to evaluate fatigue strength implements the criterion of maximum normal and shear stress on a suitable damage plane (critical plane). The angle  defining the critical plane orientation is measured with respect to the direction that maximises the applied normal stress. Eleven (11) structural materials under combined bending and torsion cyclic loading are examined. For each analysed material, the value of  angle is selected so that the value of the scatter, defined by a root-mean-square value, is minimum. On the basis of such a calculation, an empirical expression for  is proposed, that takes into account the values of bending and torsion fatigue strengths at a reference number of loading cycles. According to such an expression,  is constant for a given material.